2015
DOI: 10.1016/j.sbspro.2015.01.373
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of Hospital Information System (HIS) in Malaysian Public Hospitals

Abstract: Hospital Information System (HIS) is important to be adopted by the hospitals to improve their operations and services. Despite their importance, only 15.2% of Malaysian Public Hospitals implemented the system through THIS, IHIS and BHIS categories which shows low adoption level of HIS in Malaysia. This study aims to identify factors affecting the HIS adoption across different categories of HIS's hospitals. The finding showed that there are significant differences between factors affecting HIS adoption in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 13 publications
3
30
0
2
Order By: Relevance
“…Besides, HIS execution occurred alongside physical development under the seventh MP. Now, in total138 public hospitals in Malaysia, there are only 21 hospitals are implementing the system [7][8][9]. Along with this line, the stage of HIS adoption and performance is still in ground level [7].…”
Section: Related Workmentioning
confidence: 99%
“…Besides, HIS execution occurred alongside physical development under the seventh MP. Now, in total138 public hospitals in Malaysia, there are only 21 hospitals are implementing the system [7][8][9]. Along with this line, the stage of HIS adoption and performance is still in ground level [7].…”
Section: Related Workmentioning
confidence: 99%
“…Environmental factor is defined as the size and structure of the industry (Tornatzky & Fleischer, 1990). Several studies (n = 11) found that environmental issues influenced the electronic healthcare system (Ahmadi et al, 2015;Kuperman et al, 2013;Frisse et al, 2012;Hung et al, 2010;Ismail et al, 2015;Patel et al, 2011;53;Rudin et al, 2014;Lian et al, 2014;Sulaiman & Wickramasinghe, 2014;Ismail & Abdullah, 2016).…”
Section: Measuring Environmental Issuesmentioning
confidence: 99%
“…The previous studies (n = 8) discovered that financial resources had influenced the information systems adopted in hospitals (Ahmadi et al, 2015;Kuperman et al, 2013;Frisse et al, 2012;Hung et al, 2010). This is because implementation costs for an electronic system in the healthcare sector are high (Ismail et al, 2015;Patel et al, 2011;53;Rudin et al, 2014). This situation could occur or was reflected in the electronic information system implementation.…”
Section: Measuring Environmental Issuesmentioning
confidence: 99%
“…The use of ICTs is widespread in the health sector as well as in all other sectors which shaped by public policies. According to Ismail et al [2015], health sector in all countries is an important policy area to provide high quality services to their citizens. The services in this area need to be continuously developed and improved especially in terms of health management.…”
Section: Introductionmentioning
confidence: 99%